Examining the Impact of Brexit on Supply Chain Risk Management: Evidence from the UK Manufacturing Sector - Adelina Jucyte; Vikas Kumar; Ximing Ruan (International Journal of Organizational Business Excellence, 2021)
The 2016 Brexit Referendum in the UK resulted in a withdrawal from the EU that has brought a lot of uncertainty to the supply chains (SC) in the manufacturing sector. The manufacturing sector that operates in a highly integrated EU market and relies on a significant number of EU workers is facing sharp changes in the SC. To improve resilience to the SC risks caused by Brexit, supply chain risk management (SCRM) can play a crucial role in adopting effective strategies. Although the literature highlights both, advantages and disadvantages of Brexit, this study focuses on the potential consequences on the SC. Through a systematic literature review approach, the research aimed to analyse Brexit impact on SCRM in the manufacturing sector in the UK. The research reveals that the manufacturing sector is not resilient to a barrier to trade risk and suspending SCRM decisions in the latest sequence of political events didn’t help to improve resilience. Findings emphasize the disadvantage of stockpiling due to increased cost and reveal that reorienting SC to a domestic market from the EU could mitigate SC risks more effectively than reorienting to non-EU countries. Research also outlines specific areas where SCM should be aware such as foreign direct investment (FDI) from non-EU countries and increased rates of pay